Generations at Work: Don't Throw the Baby Out With the Bathwater. Issue 3 (2nd October 2015) - Beier, Margaret E.; Kanfer, Ruth
Abstract : Costanza and Finkelstein (2015 ) are correct to highlight the dangers of using generationally based stereotypes in organizations. Although popular, these stereotypes are related to a stigmatization based on group membership that can be pernicious and discriminatory. Costanza and Finkelstein are also correct in their assessment of the state of the literature on generational effects: theory and research is woefully lacking. Indeed, a recent review of research on generations at work characterized this research as descriptive and neither theoretical nor empirical (Lyons & Kuron, 2014 ). Yet, as pointed out by Costanza and Finkelstein, the idea of a generational identity is salient and even appealing to many people. Why would this be if it were completely devoid of psychological import? People seem to resonate with the idea that, to some extent at least, they are a product of their generation.